EFFECT OF WORD OF MOUTH (WOM) ON STUDENT DECISIONS CHOOSING PROGRAM BACHELOR DEGREE UNIVERSITY OF MUHAMMADIYAH SUMATERA UTARA WITH BRAND IMAGE AS INTERVENING VARIABLES - Mutia Arda, SE, M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
The education sector is one way to develop reliable human resources especially in universities. Along with the development of the era, universities are not only seen as a place to gain knowledge but also have a prestigious value for students who are in it. Prospective students will continue to search the information to the stage of steadfastness to enroll in the university which he thinks is best among others. The greater the risk that will be borne later in the day the more frequent students to share word of mouth. Furthermore, the consideration of prospective students is about the image of a university. This becomes very important and becomes the main capital for business developers in the field of education. A good image reflects the quality of the university. But it is not an easy matter to develop universities in Indonesia, given the intense competition with other universities. from 2015 to 2017 all faculties at the University of Muhammadiyah North Sumatra (UMSU) experienced a decrease in the number of new students by 34%. Population in this research is new student of University of Muhammadiyah Sumatera Utara (UMSU) academic year 2017/2018 as many as 3,556 students. Sampling technique in this study using proportional random sampling with a sample of 356 students. The method of analysis used in the hypothesis is path analysis. The results prove that brand image is an intervening variable between word of mouth and choosing decision. partially known that word of mouth and brand image have a significant effect on decision of choosing